Interdigitated electrode (IDE) sensor of polyaniline (PANI) nanoparticles thin film for detection of methanol vapour - Zulkhairi Zakaria (School of Materials Engineering, 2012)
This thesis reports a study on interdigitated electrode (IDE) sensor of PANI nanoparticles thin film for detection of methanol vapour. The research covers the sensor development, characterization method of PANI nanoparticles and setting up a IDE detection system.